Thermopower in Si-Ge Alloy Nanowire - Suresha, Kasala (International Journal Of Chemistry, Mathematics And Physics(IJCMP), 2023)
In this article, we studied the past and existing research in nanowire (NW) especially based on SiGe NWs. The basic Thermoelectric (TE) principles and theories are introduced and the factors that may influence the TE performance of SiGe NWs are discussed. The superiority of the group IV material-based NWs as TE materials are detailed with feasible structures while their fabrication methods and TE measurements are also reviewed. The existing SiGe NW are discussed for their potential applications and the feasible applications are illustrated. Finally, the variation of parameter TE on Temperature and carrier concentration is discussed and compare theoretically with the available experimental data.